Determinants of household broker choices and their impacts on performance - Fong, Kingsley; Krug, Juliane D.; Leung, Henry; Westerholm, Joakim P. (Journal of Banking & Finance, 2020)
We use Finnish OMX Helsinki data to examine the relationship between demographic variables, individual investors' broker choices and trade informativeness. We find that men prefer to use Full-Service-Retail over Discount-Retail brokers and that a higher level of income leads to a higher likelihood of using Discount-Retail brokers. Women present more heterogenous broker choice behaviors. However, both genders are more likely to carry out larger trades through Discount-Retail brokers. We show that trades executed via Discount-Retail brokers are more informative than those of Full-Service-Retail brokers and that only Discount-Retail brokers show trade informativeness differences across gender after controlling for age. Collectively, women make more informative trades then men, but this result reverses after partitioning by age. We conclude that conditioning on the type of broker reduces unobserved individual investor heterogeneity and that demographic variables are essential to the understanding of broker clientele effect. Furthermore, clientele differences observed across broker types are market specific and dominate the effects of financial advice in determining trade informativeness.